(3GdCHjGJ GdMSGfs
(3ChdgG (B:s
(3MeOkG def TQM def JLdi HGdHdGZI UOQkG abO CeQfi ef CeQg eWGY heNGdaJg dGJSJWGY bGSe CZG s
(3BNQgG (B:s
(3eGMc LdOc eKd XaQc aJhd CfJ LejY CeQc hEPG bUOJ dMGLI aGbUO deYJQa HbOQc JeJ GdGHjGJ GdMSGf GdeMQOI ef hajGJ GdGYjGf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs